(untitled) (Scientia Agricola, 2016)
Widely disseminated in both national and international scenarios, greenhouses are agribusiness solutions which are designed to allow for greater efficiency and control of the cultivation of plants. Bearing this in mind, the construction of greenhouses should take into consideration the incidence of wind, and other such aspects of comfort and safety, and ensure they are factored into the design of structural elements. In this study, we evaluated the effects of pressure coefficients established by the European standard EN 13031-1 (2001) and the Brazilian standard ABNT (1988), which are applicable to the structures of greenhouses with flat roofs, taking into account the following variables: roof slope, external and internal pressure coefficients and height-span ratio of the structure. Using the ANSYSTM computer program, zones of columns and roof were discretized by the Beam44 finite element to identify the maximum and minimum stress portions connected to the aerodynamic coefficients. With this analysis, we found that, in the smallest roof slope (a equal to 20°), the frame stress was quite similar for standards adopted. On the other hand, for the greatest inclination (a equal to 26°), the stress was consistently lower under the Brazilian standard. In view of this, we came to the conclusion that the differences between stresses when applying both standards were more significant at the higher degrees of height-span ratio and roof slope.